Prenatal smoking and postpartum depression: a meta-analysis - Hong-Lin Chen; Ji-Yu Cai; Man-Li Zha; Wang-Qin Shen (Taylor & Francis Group, 2019)
Objectives: Postpartum depression (PPD) is a common emotional distress among many women in diversified cultures. The aim of this study was to examine the relationship between prenatal smoking and PPD. Methods: We systematically searched PubMed, ISI Web of Science, EMBASE, Elsevier ScienceDirect, OVID and Springer databases up to 15 March 2017. The pooled odds ratio (OR) of PPD was compared between prenatal smoking women and the ones who did not smoke during pregnancy. The fixed effect model or random effect models were chosen according to heterogeneity between studies. Results: A total of 13 studies with 1,476,922 women were included in the meta-analysis. The average incidence of PPD was 3.0% (1717/57,997) in women with smoke exposure and 1.3% (6571/488,225) in women without smoke exposure. The pooled OR was 2.325 (95% CI 1.925-2.808; Z = 8.76, p < .0001) by random-effect model. The funnel plot was symmetrical, and either the Begg's test (Z = 0.92, p=.360) or the Egger's test (t = 0.04, p = .9700) suggested no publication bias among included studies. Sensitivity analysis indicated that the result was robust. Conclusion: Our meta-analysis indicated that prenatal smoking was associated with postpartum depression.